The notion and consequences of emotional abuse of a child in the family - Ljubojev Nadežda (Temida, 2004)
The paper considers the notion of emotional abuse of a child in the family as one of the most serious forms of family pathology. Emotional abuse is defined as parent’s or guardian’s acting or non acting, such as rejection insult, isolation, terror, verbal attack etc. that might cause serious and permanent disorders in child’s emotional development. Due to that, very complicated consequences of this serious form of abuse are particularly analyzed. In this paper, the author is standing up for the opinion that sexual and physical abuse are always in connection with the emotional, while emotional abuse could appear as a separate phenomenon.